2015
DOI: 10.1108/hff-03-2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady mixed convection boundary layer flow along a symmetric wedge with variable surface temperature embedded in a saturated porous medium

Abstract: Purpose – The purpose of this paper is to study laminar two-dimensional unsteady mixed-convection boundary-layer flow of a viscous incompressible fluid past a symmetric wedge embedded in a porous medium in the presence of the first and second orders resistances. Design/methodology/approach – The governing boundary-layer equations along with the boundary conditions are first converted into dimensionless form by a non-similar transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Such factors are crucial, particularly in the metallurgical processes that include the purifying of metallic materials from nonmetallic impurities and the cooling of consecutive strips and filaments dragged through a quiescent fluid. Due to its important impact in numerous fields, especially the mechanical, geomagnetic, and pesticide sciences, the research of heat transport in porous materials has recently attracted the attention of many scientists using vertical geometries by [6]. They found that a higher local Nusselt number increases the impact of viscous parameters over the surface.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Such factors are crucial, particularly in the metallurgical processes that include the purifying of metallic materials from nonmetallic impurities and the cooling of consecutive strips and filaments dragged through a quiescent fluid. Due to its important impact in numerous fields, especially the mechanical, geomagnetic, and pesticide sciences, the research of heat transport in porous materials has recently attracted the attention of many scientists using vertical geometries by [6]. They found that a higher local Nusselt number increases the impact of viscous parameters over the surface.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Also Kumari et al 10 investigated free convection boundary layer flow of a non-Newtonian fluid along a vertical wavy surface. The extension of mixed-convection boundary-layer flow along a symmetric wedge with variable surface temperature embedded in a saturated porous median was explored by Al-Harbi and Ibrahim 11 . The magneto hydrodynamics mixed convection flow over a permeable non-isothermal wedge was analyzed by Prasad et al 12 in the presence of variable thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers are particularly interested in the characteristics of unsteady Falkner-Skan wedge flow. In 2015, Saleh et al[3] considered an unsteady flow of viscous fluid towards a stretching wedge with thermal radiation effects. Alam et al[4] discussed the unsteady forced convective flow of Newtonian fluid along stretching/shrinking wedge in 2016.…”
mentioning
confidence: 99%